GLP-1 receptor agonists: an updated review of head-to-head clinical studies. (March 2021) - Trujillo, Jennifer M.; Nuffer, Wesley; Smith, Brooke A.
Glucagon-like peptide-1 receptor agonists (GLP-1 RA) are attractive options for the treatment of type 2 diabetes (T2D) because they effectively lower A1C and weight while having a low risk of hypoglycemia. Some also have documented cardiovascular benefit. The GLP-1 RA class has grown in the last decade, with several agents available for use in the United States and Europe. Since the efficacy and tolerability, dosing frequency, administration requirements, and cost may vary between agents within the class, each agent may offer unique advantages and disadvantages. Through a review of phase III clinical trials studying dulaglutide, exenatide twice daily, exenatide once weekly, liraglutide, lixisenatide, semaglutide, and oral semaglutide, 14 head-to-head trials were identified that evaluated the safety and efficacy of GLP-1 RA active comparators. The purpose of this review is to provide an analysis of these trials. The GLP-1 RA head-to-head clinical studies have demonstrated that all GLP-1 RA agents are effective therapeutic options at reducing A1C. However, differences exist in terms of magnitude of effect on A1C and weight as well as frequency of adverse effects.